Center‐level trends in utilization of HCV‐exposed donors for HCV‐uninfected kidney and liver transplant recipients in the United States. Issue 8 (9th April 2019) - Bowring, Mary G.; Shaffer, Ashton A.; Massie, Allan B.; Cameron, Andrew; Desai, Niraj; Sulkowski, Mark; Garonzik‐Wang, Jacqueline; Segev, Dorry L.
Abstract : Several single‐center reports of using HCV‐viremic organs for HCV‐uninfected (HCV‐) recipients were recently published. We sought to characterize national utilization of HCV‐exposed donors for HCV‐ recipients (HCV D+/R−) in kidney transplantation (KT) and liver transplantation (LT). Using SRTR data (April 1, 2015‐December 2, 2018) and Gini coefficients, we studied center‐level clustering of 1193 HCV D+/R− KTs and LTs. HCV‐viremic (NAT+) D+/R− KTs increased from 1/month in 2015 to 22/month in 2018 (LTs: 0/month to 12/month). HCV‐aviremic (Ab+/NAT‐) D+/R− KTs increased from < 1/month in 2015 to 26/month in 2018 (LTs: <1/month to 8/month). HCV‐ recipients of viremic and aviremic kidneys spent a median (interquartile range [IQR]) of 0.7 (0.2‐1.6) and 1.6 (0.4‐3.5) years on the waitlist versus 1.8 (0.5‐4.0) among HCV D−/R−. HCV‐ recipients of viremic and aviremic livers had median (IQR) MELD scores of 24 (21‐30) and 25 (21‐32) at transplantation versus 29 (23‐36) among HCV D−/R−. 12 KT and 14 LT centers performed 81% and 76% of all viremic HCV D+/R− transplants; 11 KT and 13 LT centers performed 76% and 69% of all aviremic HCV D+/R− transplants. There have been marked increases in HCV D+/R− transplantation, although few centers are driving this practice; centers should continue to weigh the risks and benefits of HCV D+/R− transplantation. Abstract : Utilization of HCV‐exposed (Ab+/NAT‐ and NAT+) deceased donor livers and kidneys for transplant in recipients without evidence of HCV occurring outside of clinical trials has increased substantially across the United States since 2015, yet remains clustered within a small number of centers.